Evaluation of the resistance of the breeding material beetroot to Cercospora amid epiphytoty in greenhouses the Moscow region - E. G. Kozar; S. A. Vetrova; I. A. Engalycheva; M. I. Fedorova (Овощи России, 2019)
Relevance. An important feature that determines the technological qualities of varieties and hybrids of beetroot is an erect, compact leaf rosette that persists until the end of the vegetation of plants. In this regard, much attention is paid to the selection of resistance to diseases affecting the leaves of plants, including Cercospora beticola Sacc. When creating resistant to Cercospora interline hybrids based on CMS, the selection of parent components plays an important role. In agroclimatic conditions of the Moscow region, Cercospora on industrial beetroot rarely reaches an economically significant threshold of harmfulness. However, in 2019, epiphytic development of Cercospora on summer first-year crops was observed in the block film greenhouse of the «Federal Scientific Vegetable Center», which allowed to assess the promising breeding material.Material and method. Phytomonitoring on beetroot plantings and sowing of the experimental production Department of the «Federal Scientific Vegetable Center» growing was carried out by methods of visual diagnostics and microscopy. Cercospora lesion in the breeding nursery was evaluated on an 11-point scale, the ranking of samples into five groups of resistance - according to the degree of disease development (R%). Analyzed: 28 sterile lines (А); 13 fertile lines of fixers (В); 25 lines of pollinators (С) and 38 hybrid F1 (АхВхС).Results. It was found that more than half of the studied lines were receptive to Cercospora. The share of relatively resistant lines was 13%. Most of them (8%) are ms - lines « obtained by pollination of CMS with mf-lines В. A close relationship (r=0.86-0.89) between the index of lesion of fixators and the degree of disease development of ms- lines was revealed, in some simple combinations a positive effect of heterosis on resistance to Cercospora relative to mf-В was noted. In the submitted sample F1 hybrids mainly observed between the nature of inheritance according to the degree of disease development (R, %), mixed effects the base line stability of pollinator mf-С (r=0,32) and a closer correlation of the stability of hybrid offspring the F1 with the resistant parent ms-line А (r=0.55). As a result of the evaluation, the most resistant to Cercospora ms- and mf-lines and derived from them hybrid F1, among which only 9% were included in the group of relatively resistant to C. beticola.